Determinação da teor de proteínas e da concentração total e concentração bioacessível de Fe e Zn em castanha de caju (Anacardium ocidentale L.) - Xavier, Alexsandra Dias de Souza [UNIFESP] (2018)
This project aimed to quantify the total and bioaccessible fraction of iron and zinc; extracting and quantifying the protein fractions (albumins, globulins, glutamines and prolamins) associated with these elements; subjecting them to the acetone precipitation step and analyzing the iron and zinc fraction associated to proteins (metalloproteins) and also their bioaccessible fractions. The total amount of these metals was evaluated by flame atomic absorption spectrometry (FAAS), using a validated method that was verified by following merits figures: linear working range, LOD, LOQ, matrix effect evaluation and evaluation of the certified material. The total concentration of Fe and Zn in cashew nut was 55.0 ± 1.2 mg kg-1 and 41.0 ± 0.1 mg kg-1 , respectively. The bioaccessibility essay was done in the sample and the results showed that 36% of Fe and 32% of Zn was bioaccessible. The total protein concentration was determined by an elemental analyzer (CNHS) and the fractions, obtained from a sequential extraction procedure (albumins, globulins, glutelins and prolamins), was done by Bradford’s method. The results obtained by CNHS showed that cashew nut has 22.1% of total proteins. However, the content obtained from sequential extraction showed that 16.5% of albumins, 6.9% of globulins, 8% of glutelins and 0.1% of prolamins. The determination of Fe and Zn by FAAS in each extracts reveals that 16% of Fe may be associated with albumins, 37% with globulins and only 8.4% of this analyte was associated to glutelin. For zinc there was 21.5% in albumin extract solution, 11.71% associated with globulins, 4.73% with glutelins, and the Zn content in the solution containing prolamins was below LD. The results obtained from evaluation of bioaccesibility of Fe and Zn in precipitated obtained after a coagulation process with acetone showed that a small quantity of these elements was bioaccessible. Therefore, a part of these metals remain associated with proteins even after the simulated digestion process and are not bioaccessible.